Fables. Werewolves of the heartland - Willingham, Bill (DC Comics/Vertigo, 2012)
Bigby Wolf embarks on a quest through the American Heartland to find a new location for Fabletown, a secret society of exiled fairy tale characters living among the "mundys." In his wanderings, Bigby stumbles across Story City, a small town that seems to be occupied solely by werewolves. Oddly enough, they seem to already know and revere Bigby, but at the same time they've captured and caged him.